Comparative Efficacy of Atorvastatin and Guggul in LDL-C Reduction: A Randomized Clinical Trial - Lodangi Nagakrishna; Dr. Akash Vishwe, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Hyperlipidemia is a major risk factor for cardiovascular diseases (CVD), necessitating effective lipid-lowering strategies. While atorvastatin remains the first-line treatment for LDL-C reduction, statin intolerance limits its long-term use in some patients. This study aimed to compare the efficacy of atorvastatin and Guggul (Commiphora mukul) in reducing LDL-C levels. A 12-week, randomized controlled trial (RCT) was conducted on 150 patients with hyperlipidemia, divided into atorvastatin (10 mg/day) and Guggul (2000 mg/day) groups. The atorvastatin group exhibited a 26.3% reduction in LDL-C, significantly higher than the 15.3% reduction in the Guggul group (p < 0.001). HDL-C increased by 11.0% and 12.9% in atorvastatin and Guggul groups, respectively, with no significant difference between the two (p = 0.08). While atorvastatin remains superior in LDL-C reduction, Guggul demonstrated moderate lipid-lowering efficacy with a better safety profile, suggesting its potential role as an alternative for statin-intolerant patients.